Tradisi Ziarah Kubur ke Makam Sunan Ampel Sebagai Upaya Meningkatkan Ketakwaan Kepada Allah SWT - Anantia Aulia Srirahma Devi (Jurnal Budi Pekerti Agama Islam, 2024)
The phenomenon of grave pilgrimage has a rich historical background. Polemic discussions about this incident have been going on for quite a long time, since Ibn Taymiyah in the 12th century and Muhammad bin Abdul Wahab in the 20th century. It is important to know that grave pilgrimage not only includes ritualistic aspects of worship, but also social, political and even commercial aspects. One of the places that is often visited for grave pilgrimages is the grave of Sunan Ampel. The grave pilgrimage to the Sunan Ampel Tomb also brings various benefits, including visiting a person's grave as an Islamic heritage, increasing his devotion to Allah SWT and fostering a virtuous life and a true Muslim personality.